Decolonizing global mental health :the psychiatrization of the majority world - Mills, China (London Taylor and Francis, 2014)
"Decolonizing Global Mental Health offers a critical postcolonial reading of this newly emerging arena, with a particular focus on psychology's and psychiatry's encounters with, and responses to, distress or 'mental illness' in low-income countries. The World Health Organisation and the Movement for Global Mental Health currently push for the 'scale-up' of psychiatric and psychological interventions on to low-income countries, modelled on those from high-income countries. However critiques of psychiatric and psychological services from service users, the survivor movement and professionals, often remain invisible within 'Global Mental Health' literature. This book argues that it is imperative to explore how this alternative 'evidence base' might be mobilized to fruitfully interrogate calls to 'scale up' psychiatric and psychological services in the majority world. The book seeks to de-familiarize current 'Western' conceptions of psychology and psychiatry using postcolonial theory, and seeks to bring into focus a series of questions and problematizations. As such it is ideal reading for undergraduate and postgraduate students, as well as researchers in the fields of critical psychology and psychiatry, social and health psychology, cultural studies, public health and social work"--
"This book offers a critical post-colonial reading of the newly emerging arena of global mental health; with particular focus on psychology's and psychiatry's encounters with, and responses to, distress or 'mental illness' in low-income countries. The World Health Organisation and the Movement for Global Mental Health currently push for the 'scale-up' of psychiatric and psychological interventions onto low-income countries, modelled on those from high-income countries (such as the UK). However critiques of psychiatric and psychological services from service users, the survivor movement and professionals from many high-income countries, often remain invisible within 'Global Mental Health' literature. This book argues that it is imperative to explore how this alternative 'evidence base' might be mobilised to fruitfully interrogate calls to 'scale-up' psychiatric and psychological services in low-income countries. The book seeks to de-familiarise current 'Western' conceptions of psychology and psychiatry using post-colonial theory, and seeks to bring into focus a series of questions and problematisations. As such it is ideal reading for undergraduate and postgraduate students, as well as researchers in the fields of critical psychology and psychiatry, social and health psychology, cultural studies, public health and social work"--
Keywords: Mental health policy; Psychiatry, Transcultural; Mental health services; World health